The genus chionanthus l. (oleaceae) in Malesia III. The Sabah species - Kiew, Ruth (Forestry Department Peninsular Malaysia, 1981)
Thirteen species are recorded for Sabah. The three species endemic to Sabah (C. pubicalyx (Ridley) Kiew comb. nov. and two new species, C. crispus and C. lucens) are described and an annotated key for the identification of all species is provided. Chionanthus cuspidatus Bl., C. longipetalus (Merr.) Kiew, Co oliganthus (Merr.) Kiew, C. plurifiorus (Knobl.) Kiew and C. porcatus Kiew are endemic to Borneo; C. elaeocarpus (Stapf) Kiew, C. evenius (Stapf) Kiew, C. laxiflorus Bl. and C. platycarpus (K.& G.) Kiew are recorded from Borneo and Malaya (the latter is a new record for Borneo). Only C. ramifiorus Roxb. is widespread throughout Malesia.